New Polyether Triterpenoids from Laurencia viridis and Their Biological Evaluation - Pacheco, Francisco Cen (Molecular Diversity Preservation International, 2011)
The red seaweed Laurencia viridis is a rich source of secondary metabolites derived from squalene. New polyethers, such as iubol (2), 22-hydroxy-15(28)- dehydrovenustatriol (3), 1,2-dehydropseudodehydrothyrsiferol (4), and secodehydrothyrsiferol (5) have been isolated and characterized from this alga. The structures were determined through the interpretation of NMR spectroscopic data and the relative configuration was proposed on the basis of NOESY spectrum and biogenetic considerations. All new compounds exhibited significant cytotoxic activity against a panel of cancer cell lines.